Emboldening dexterity digital bookkeeping-accounting and brand craft: Summoning the intellectual and visual assets quirks - Lakilaki, Eogenie (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2025)
This study examines Sedekah Laksan, an integrated programme addressing persistent financial and branding literacy gaps among rural micro, small, and medium enterprises (MSMEs) in Indonesia. Rural MSMEs face limited digital access, weak financial practices, and poor brand identity—obstacles to sustainable growth. Using a participatory action research (PAR) design, the intervention combined training workshops, onsite mentoring, and digital tools such as Google Spreadsheets and Excel-based templates to enhance digital accounting and branding skills. Data were collected via pre-post surveys, performance assessments, and field observations. Quantitative results, supported by paired t-tests and large Cohen’s d values (>1.2), indicate substantial improvements in financial literacy, brand design, and entrepreneurial self-efficacy. Beyond technical gains, participants demonstrated behavioural changes, including independent financial planning and consistent digital branding. These findings affirm the value of culturally grounded, dual-focus interventions in building MSME resilience. The study recommends scalable models incorporating artificial intelligence (AI) for adaptive learning and automated financial advice, while accounting for infrastructure and digital literacy constraints in rural settings. The intervention illustrates how digital skills—framed as both visual and intellectual assets—can strategically empower rural entrepreneurs and foster long-term socio-economic inclusion.